Factors Affecting Satisfaction and Loyalty of Online Taxi-Motor Partners - Luvy Mayanda; Hari Wijayanto; Istiqlaliyah Muflikhati (Indonesian Journal of Business and Entrepreneurship (IJBE), 2018)
A growing number of online motorcycle taxi is impacting a greater competition in its business to the extent that a business partner of the motorcycle taxi contributes a significant portion in the business. The purpose of this journal was to observe the influence of satisfaction level on partner loyalty in online taxi-motor application company in Bekasi city. The levels of satisfaction and loyalty of the business partner were measured by using CSI and CLI methods. 125 business partners, operating in Bekasi, became the respondents in this analysis based on Slovin method with 10% error margin. SEM methods were utilized to analyze the influence of the business partner characteristics on the level of satisfaction and the impact of level of satisfaction on business partner loyalty. In addition, IPA was used to analyze the significant attributes of business partner's level of satisfaction. CSI and CLI findings show that the business partners are within the satisfactory level and high loyalty towards its current partnership. SEM analysis reveals that there is a strong influence between the level of partner's satisfaction and loyalty. Better provision of trip rates has become a significant indicator for business partner during the partnership process which was examined by IPA method.Keywords: online transportation, satisfaction index, loyalty index, IPA, CSI